The subjects and meanings of young children's drawings - Coates, Elizabeth; Coates, Andrew (Exploring Children's Creative Narratives, 2011)
In 1955 Rhoda Kellogg in America suggested that: The reality objects drawn by children under five years of age are ones which most easily evolve out of their earlier abstractions and are recognisable by adults as well as by the child. Autos, boats, flowers, airplanes soon join the sun, human, animal and house. These objects then get compiled into one drawing. (Kellogg 1959: 119) Our examination of upwards of 800 drawings and related audiotape recordings, collected as a result of an ongoing research project observing three to seven year old children, in pairs, making self-directed drawings (in other words, making images of subjects of their own choice) (Coates and Coates 2006) although supporting in principle the production of Kellogg's 'reality objects', has provided valuable insights into children's thinking about their works which goes beyond her simple definition of theme and content. In this chapter we argue that the narratives that accompany these drawings provide evidence of individual trains of thought which not only derive from significant first-hand experiences but also indicate a highly complicated and informed knowledge and understanding of contemporary popular visual culture. Aspects of this may well include picture books produced specifically for children as role models for the successful marriage of Plate and story, television cartoons in which inanimate objects and animals achieve human status by acquiring language, characters on television and DVD/video productions such as Darth Vader and Sleeping Beauty which provide experiences and stories outside children's normal potential to imagine, and television documentaries containing facts and insights into a range of subjects and diverse cultures. It would seem, therefore, that this enriched cultural awareness has had a profound influence on children's drawings as it has enabled them to extend their subject matter beyond the boundaries of first-hand experience.